The Values of The Ukhwah Trilogy in The Qur’an and Its Relevance for Deradicalization Efforts - Tahir, Muhammad Suaib (KALAM, 2023)
The value of ukhuwah is often understood as a teaching of brotherhood that applies to fellow groups or religions only. The main focus in this study is the values of the Ukhuwwah Trilogy: ukhuwwah Islamiyyah (brotherhood among Muslims), ukhuwwah basyariyyah (brotherhood among mankind), as well as ukhuwwah wathaniyah (brotherhood in national bonds). This research is a literature study using descriptive methods and a contextual interpretation approach. The result provides that the verses of the Qur’an talking about ukhuwah has implications for the meaning of social relations which are not only about teachings and rules relating to fellow Muslims, but also the values of brotherhood among human beings which are an important factor in creating internal and inter-religious harmony. So that the values contained in the ukhuwah verses can be used as guidelines in deradicalization efforts. These verses also have implications for meaning as guidelines for living side by side by establishing good communication with anyone based on humanity (basyariyyah). The main goal is also to maintain good relations between citizens based on nationalism.